Intermolecular effects on tunneling through acenes in large-area and single-molecule junctions - Liu, Yuru; Ornago, Luca; Carlotti, Marco; Ai, Yong; El Abbassi, Maria; Soni, Saurabh; Asyuda, Andika; Zharnikov, Michael; van der Zant, Herre S. J.; Chiechi, Ryan C. (The journal of physical chemistry. C, Energy, materials, and catalysis, 2020)
This paper describes the conductance of single-molecules and self-assembled monolayers comprising an oligophenyleneethynylene core, functionalized with acenes of increasing length that extend conjugation perpendicular to the path of tunneling electrons. In the Mechanically Controlled Break Junction (MCBJ) experiment, multiple conductance plateaus were identified. The high conductance plateau, which we attribute to the single molecule conformation, shows an increase of conductance as a function of acene length, in good agreement with theoretical predictions. The lower plateau is attributed to multiple molecules bridging the junctions with intermolecular interactions playing a role. In junctions comprising a self-assembled monolayer with eutectic Ga-In top-contacts (EGaIn), the pentacene derivative exhibits unusually low conductance, which we ascribe to the inability of these molecules to pack in a monolayer without introducing significant intermolecular contacts. This hypothesis is supported by the MCBJ data and theoretical calculations showing suppressed conductance through the PC films. These results highlight the role of intermolecular effects and junction geometries in the observed fluctuations of conductance values between single-molecule and ensemble junctions, and the importance of studying molecules in both platforms.